Aristotle's Delphic Knife. - O'Rourke Boyle, Marjorie (Journal of Religion, 2024)
The subject of this article is the classical Greek history of religion, particularly ritual sacrifice in relation to political ethics. This article recovers the lost meaning of the Delphic knife made by coppersmiths that Aristotle's Politics (1.2 1252b) contrasted with the city famously made by Nature. It dismisses traditional conjectures about the knife as historically inaccurate about its craft and philosophically uninformed about Aristotle's doctrine of the final cause, or purpose, of making something. It states the obvious purpose of a knife as cutting, which Aristotle skillfully practiced as the first anatomist, or dissector. It documents the purpose of a classical Greek ritual knife to divide the carcass of a sacrificed animal into equitable portions for civic distribution. It identifies Neoptolemus, the legendary hero turned villain, who was stabbed during his sacrifice at Delphi as an exemplar of greed in quarreling with the temple butcher for an excessive share of the allotted meat. Aristotle alluded to the popular drama and poetry about his and other violations of the Delphic maxim "nothing in excess." His Politics argued against political factions as greedy, thus divisive of the city that Nature made a whole. He approved of ritual sacrifice as a civic bond, and he taught civic moderation in conformity with his well-known ethics of personal moderation.